아동의 PPARGC1A 유전자형(Gly482Ser)과 신체활동, 비만지표, 대사성위험인자와의 연관성 - 안의수; 최규환; 조진경; 하창덕; 강현식 (Exercise science (Seoul, Korea), 2012)
본 연구의 목적은 peroxisome proliferator activated receptor–γ coactivator–1α (PPARGC1A) 유전자의 Gly482Ser 단일염기다형성(SNP)이 아동의 비만지표와 대사성위험인자에 미치는 영향을 검정하는 것으로 하였다. 경기도 지역 초등학생 283명(남=150, 여=133, 연령：8-12세)을 대상으로 하였으며, PPARGC1A유전자 Gly482Ser SNP 분석은 TaqMan probe를 이용한 allelic discrimination assay법을 이용하였다. 측정변인으로는 신체활동량과 비만지표(체중, 신장, 체질량지수, 체지방율, 허리·엉덩이 둘레비율) 그리고 대사성위험인자(혈압, 총 콜레스테롤, 고밀도지단백콜레스테롤, 중성지방, 혈당, 인슐린, 호마지수)로 하였으며, Gly482Ser SNP(Gly482Gly, Gly482Ser, Ser482Ser)에 따른 모든 측정변인들의 차이를 검정하기 위해 일원분산분석법과 bonferroni 사후검정을 이용하였다. 본 연구 결과, Ser482Ser 집단이 Gly482Gly 및 Gly482Ser 집단에 비해 체중(p=.016), 체지방율(p=.009), 엉덩이 둘레(p=.038) 그리고 체질량지수(p=.090)가 유의하게 높은 것으로 나타났다. 결론적으로, PPARGC1A 유전자의 Gly482Ser SNP 중 Ser482Ser 유전자형을 가진 아동은 비만에 대한 위험이 상대적으로 높은 것으로 판단되기에 비만 예방을 위한 더 많은 관리와 노력이 필요할 것으로 생각된다. The purpose of the study was to investigate the genetic effect of the PPARGC1A gene on body fatness and metabolic risk factors in Korean children. A single nucleotide polymorphism (SNP) of Gly482Ser(rs8192678) in the PPARGC1A gene was genotyped by using a Taqman assay in a total of 283 children (boys=150 & girls=133, aged 8 to 12 years) who were recruited from local elemental schools. Primary outcomes of the study included body composition parameters including weight, height, body mass index, waist circumference, percent body fat and waist-to-hip ratio and metabolic risk factors including resting blood pressures, triglycerides, total cholesterol, high-density lipoprotein cholesterol, fasting glucose, insulin and homeostasis assessment model of insulin resistance(HOMA-IR). One-way ANOVA followed by bonferroni post-hoc tests was used to test any significant associations between the measured variables and genotype at a statistical significance of p=.05. The Ser482Ser genotype had significantly higher values in body weight (p=.016), percent body fat (p=.009), hip (p=.038) and body mass index (p=.090) than either the Gly482Gly or Gly482Ser genotype. The findings of the study suggest that the Ser482Ser genotype might play as a predisposed risk for obesity in Korean children. KCI Citation Count: 0